Pregnancy outcomes in women with endometriosis: a national record linkage study. (16th February 2016) - Saraswat, L; Ayansina, DT; Cooper, KG; Bhattacharya, S; Miligkos, D; Horne, AW; Bhattacharya, S
Abstract : Objective: To determine pregnancy outcomes in women with endometriosis. Design: A national population based cohort study using record linkage. Setting: Scotland. Participants: A cohort of 14 655 women followed up over a 30‐year period (1981–2010). Methods: In a nationwide Scottish study, we compared pregnancy outcomes in 5375 women with surgically confirmed endometriosis with outcomes in 8710 women without endometriosis who were pregnant during the same time period. Data were analysed using univariable and multivariable logistic regression after adjusting for confounding factors. Main outcome measures: Outcome measures evaluated included miscarriage, ectopic pregnancy, stillbirths and other pregnancy complications such as hypertensive disorders of pregnancy, antepartum and postpartum haemorrhage, operative delivery and preterm births. The outcomes were presented as adjusted odds ratios (OR) with 95% confidence intervals (CI). Results: On multivariable analysis, after adjusting for age, parity, socio‐economic status and year of delivery, women with endometriosis when compared to women without endometriosis, had a significantly higher risk of early pregnancy complications with adjusted OR (95% CI) of 1.76 (1.44, 2.15) and 2.70 (1.09, 6.72) for miscarriage and ectopic pregnancy, respectively. A previous diagnosis of endometriosis was associated with a significantly increased risk of [adjusted OR (95% CI)] placenta praevia [2.24 (1.52, 3.31)], unexplained antepartum haemorrhage [1.67 (1.39, 2.00)], postpartum haemorrhage [1.30 (1.61, 1.46)] and preterm births [1.26 (1.07, 1.49)] in pregnancies progressing beyond 24 weeks. Conclusion: Endometriosis predisposes women to an increased risk of early pregnancy loss and later pregnancy complications. Tweetable abstract: Endometriosis predisposes women to an increased risk of early pregnancy loss and later pregnancy complications. Tweetable abstract: Endometriosis predisposes women to an increased risk of early pregnancy loss and later pregnancy complications.